Harnessing African stock exchanges to promote growth - Masimba Tafirenyika (Africa Renewal, 2012)
Days before Facebook became a public company on 18 May, the hype behind the social network giant went into overdrive. The media proclaimed it the biggest ever stock market flotation by an Internet company. Investors salivated over a rare chance to make quick profits. The 900 million plus fans who had turned Facebook into a global giant wondered publicly what was in it for them. For a while, it wasn’t just seasoned investors eyeing the stock; even the public showed momentary interest.